2010
DOI: 10.1208/s12249-010-9391-2
|View full text |Cite
|
Sign up to set email alerts
|

Naked Plasmid DNA Formulation: Effect of Different Disaccharides on Stability after Lyophilisation

Abstract: Since plasmid DNA (pDNA) is unstable in solution, lyophilisation can be used to increase product shelf life. To prevent stress on pDNA molecules during lyophilisation, cryo- and lyoprotectants have to be added to the formulation. This study assessed the effect of disaccharides on naked pDNA stability after lyophilisation using accelerated stability studies. Naked pDNA was lyophilised with sucrose, trehalose, maltose or lactose in an excipient/DNA w/w ratio of 20. To one part of the vials extra residual moistur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…The interest in preserving DNA as dried preparations has increased vastly in response to the growing demand from a variety of fields, including pharmaceutical sciences [56,82,91,113,121,122], forensics [123], molecular diagnostics [124], and biorepository management [125]) for storing DNA samples or tumor specimen banks [114,126] for prolonged periods of time, sometimes in large numbers, in regions where sophisticated storage equipment may not be available. Although the requirements are quite different in each of these fields, the need for strategies that provide highly stable storage conditions (e.g., room temperature storage) seems to be a common factor.…”
Section: Preservation Of Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…The interest in preserving DNA as dried preparations has increased vastly in response to the growing demand from a variety of fields, including pharmaceutical sciences [56,82,91,113,121,122], forensics [123], molecular diagnostics [124], and biorepository management [125]) for storing DNA samples or tumor specimen banks [114,126] for prolonged periods of time, sometimes in large numbers, in regions where sophisticated storage equipment may not be available. Although the requirements are quite different in each of these fields, the need for strategies that provide highly stable storage conditions (e.g., room temperature storage) seems to be a common factor.…”
Section: Preservation Of Dnamentioning
confidence: 99%
“…However, DNA must resist the freezing and drying stresses encountered during processing before stability can be addressed. In this respect, it has been demonstrated that the addition of disaccharides, such as sucrose and trehalose, are beneficial to prevent loss of SC DNA during lyophilization [55,56,82,91,96,113,115,121,178,179].…”
Section: Stability Of Dried Plasmid Dnamentioning
confidence: 99%
“…For TRH (D-(þ)-trehalose dehydrate, Fluka Analytical, Buchs, Switzerland) final concentrations of 0.07% TRH (w/v) e corresponding to a ratio of 20/1 TRH/oligo nucleic acid according to Quaak, Haanen, Beijnen, and Nuijen (2010) e and 4.17% TRH (w/v) were used. For gelatine (GEL; Perfect Block Gelatine, MoBiTec GmbH, Göttingen, Germany), final concentrations of 0.1% GEL (w/v) and 0.17% GEL (w/v) and for polyethylene glycol (PEG 8000; Fluka Analytical Biochemica, Buchs, Switzerland) final concentrations of 0.5% PEG (w/v), 1.5% PEG (w/v) and 8% PEG (w/v) were applied.…”
Section: Storage Experimentsmentioning
confidence: 99%
“…In general, solid proteins are the preferred mode of storage, since in solution dosage forms, proteins and even plasmid DNA are relatively unstable (1,2). A minimum amount of water is required for maintaining the three-dimensionally folded native conformation of a protein in the solid state.…”
Section: Introductionmentioning
confidence: 99%